Language Study On Power Relations Between Kiai and Santri in Islamic Boarding School - Aidy Samrolis; Rosyida Ekawati (Universitas Musamus Merauke, 2022)
This study is intended to describe the language elements used by Kiai and Santri and how language elements show power relations between Kiai and Santri in Banyuanyar Islamic Boarding School. This study uses descriptive qualitative method. The source of data of this study is Kiai and Santri in Banyuanyar Islamic Boarding School. The data of this study is the utterances between Kiai and Santri which contains power relations. The data is taken in Banyuanyar Islamic Boarding School by observing the activities within a day. The writer conducted this study by using theory of Fairclough and supported by Van Dijk’s theory. The result of this study shows that the language elements: pronoun, modality, and transitivity used by Kiai and Santri to show power relation. It is found 2 pronouns as address terms used such as ‘cong’(kid) and ‘be’en (you).’ There are 11 data used pronoun ‘cong’ and 4 data used pronoun ‘be’en.’ The use of modality is found in 1 data of modulation and 2 data of modalization. The transitivity element used in the utterances are 7 mental processes, 6 material processes, 4 verbal processes, and 1 relational process. The result of this study shows Santri can empower Kiai in term of rejection.